ANALYSIS OF NGEBEL LAKE VISITORS' SATISFACTION USING IMPORTANCE-PERFORMANCE ANALYSIS (IPA) APPROACH - Dian Pratiwi; Muhammad Imron (MESP–FEB UNS, 2019)
The development of tourist areas is commonly targeted as a backbone sector to support economic growth, increase regional income, empower the economy of the community, expand employment, and improve the overview and marketing of local products of tourist destinations to improve local community welfare. This development requires holistic and comprehensive planning in order to optimize the benefits for the local community and contribute to the regional income of a region. Ngebel Lake, one of the tourist attractions in East Java, has a considerable potential to be developed into a leading lake tourist destination. Located in Ponorogo Regency, this place is prospective for its pristine natural beauty and other favorable elements such as culture, community lifestyle, and the potential as a tourist attraction. The half kilometer-wide lake was naturally formed and is surrounded by a five-kilometer road. This study aimed at analyzing the satisfaction of Telaga Ngebel visitors as an effort to identify satisfaction attribute on service quality using Importance-Performance Analysis (IPA). This approach was aimed to provide recommendations in evaluating visitors’ satisfaction. The research was not merely targeted to identify whether visitors’ expectations were already accomplished, but it was aimed to identify the functional and dysfunctional attributes of service.The results have shown that the attributes requiring improvements include the availability of adequate parking lots, the quality of roads around the tourist area, and the willingness of the staff to prioritize and recognize the needs of visitors. This research is the first step in setting recommendations for strategies that can become local government priorities in the development of the Ngebel Lake tourist area. Keywords: Visitors’ satisfaction, Importance-Performance Analysis (IPA)